Self-esteem and Self-efficacy Association With Condom Use among Male Who Having Sex With Male (MSM) - Mohd Hafizuddin Ahmad; Fredie Robinson; Nachia Banu Abdul Rahim (Universiti Putra Malaysia, 2023)
Introduction: A significant increase in HIV cases among male who having sex with male (MSM) population from 2010 until 2020 has confirmed that sexual behaviour is a primary factor of exposure to sexually transmitted infections (STIs), with condom use behaviour as the dominant risk factor. This study aim to identify factors associated with consistent condom use among MSM in Sabah. Methods: This was a cross-sectional study carried out among MSM in Sabah. Information on sociodemographics, self-esteem, self-efficacy regarding condom use, and condom use behaviour during the last sex was collected using a Google Form survey. Results: The prevalence of consistent condom use during last sexual intercourse among 331 MSM was 26.3%. From the multivariate analysis, consistent condom use was associated with Chinese ethnicity (aOR = 5.557; 95% CI = 1.533 – 20.147), unmarried (aOR = 17.251; 95% CI = 6.709 – 44.355), unemployment (aOR = 8.375; 95% CI = 2.385 – 29.409), and condom use self-efficacy (aOR = 1.069; 95% CI = 1.045 – 1.094). Conclusion: Chinese ethnicity, unmarried, unemployment, and condom use self-efficacy were significantly related to consistent condom use among respondents. The utilization of comprehensive prevention programs, including interventions targeting psychological factors and increasing access to condoms, may promote safe sex behaviour and reduce STIs among MSM.